Chemistry, pharmacology, and cellular uptake mechanisms of thiometallate sulfide donors. (23rd May 2019) - Durham, Tom; Zander, David; Stomeo, Niccolò; Minnion, Magdalena; Hogarth, Graeme; Feelisch, Martin; Singer, Mervyn; Dyson, Alex
Abstract : Background and Purpose: A clinical need exists for targeted, safe, and effective sulfide donors. We recently reported that ammonium tetrathiomolybdate (ATTM) belongs to a new class of sulfide‐releasing drugs. Here, we investigated the cellular uptake mechanisms of this drug class compared to sodium hydrosulfide (NaHS) and the effects of a thiometallate tungsten congener of ATTM, ammonium tetrathiotungstate (ATTT). Experimental Approach: In vitro H2 S release was determined by headspace gas sampling of vials containing dissolved thiometallates. Thiometallate and NaHS bioactivity was assessed by spectrophotometry‐derived sulfhaemoglobin formation. Cellular uptake dependence on the anion exchange protein (AE)‐1 was investigated in human red blood cells. ATTM/glutathione interactions were assessed by LC–MS/MS. Rodent pharmacokinetic and pharmacodynamic studies focused on haemodynamics and inhibition of aerobic respiration. Key Results: ATTM and ATTT both exhibit temperature‐, pH‐, and thiol‐dependence of sulfide release. ATTM/glutathione interactions revealed the generation of inorganic and organic persulfides and polysulfides. ATTM showed greater ex vivo and in vivo bioactivity over ATTT, notwithstanding similar pharmacokinetic profiles. Cellular uptake mechanisms of the two drug classes are distinct; thiometallates show dependence on AE‐1, while hydrosulfide itself was unaffected by inhibition of this pathway. Conclusions and Implications: The cellular uptake of thiometallates relies upon a plasma membrane ion channel. This advances our pharmacological knowledge of this drug class, and further supports their utility as cell‐targeted sulfide donor therapies. Our results indicate that, as a more stable form, ATTT is better suited as a copper chelator. ATTM, a superior sulfide donor, may additionally participate in intracellular redox recycling. Linked Articles: This article is part of a themed section on Hydrogen Sulfide in Biology & Medicine. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.4/issuetoc